Living Matter: The Preservation of Biological Materials in Contemporary Art: An International Conference Held in Mexico City, June 3–5, 2019 - Living Matter (Conference) (2019 : Mexico City, Mexico); Rivenc, Rachel; Roth, Kendra; Getty Conservation Institute; Universidad Nacional Autónoma de México. Museo Universitario Arte Contemporáneo; Escuela Nacional de Conservación, Restauración y Museografía "Prof. Manuel del Castillo Negrete" (Mexico) (J. Paul Getty Trust, The, 2022)
This innovative volume is the first to address the conservation of contemporary art incorporating biological materials such as plants, foods, bodily fluids, or genetically engineered organisms. Eggshells, flowers, onion peels, sponge cake, dried bread, breast milk, bacteria, living organisms-these are just a few of the biological materials that contemporary artists are using to make art. But how can works made from such perishable ingredients be preserved? And what logistical, ethical, and conceptual dilemmas might be posed by doing so? Because they are prone to rapid decay, even complete disappearance, biological materials used in art pose a range of unique conservation challenges. This groundbreaking book probes the issues associated with displaying, collecting, and preserving these unique works of art. The twenty-four papers from the conference present a range of case studies, prominently featuring artists' perspectives, as well as conceptual discussions, thereby affording a comprehensive and richly detailed overview of current thinking and practices on this topic. Living Matter is the first publication to explore broadly the role of biological materials in the creative process and present a variety of possible approaches to their preservation. The free online edition of this open-access publication is available at www.getty.edu/publications/living-matter/ and includes videos and zoomable illustrations. Also available are free PDF, EPUB, and Kindle/MOBI downloads of the book.